A cat in Paris [videorecording (DVD)] - Felicioli, Jean-Loup; Felicioli, Jean-Loup; Felicioli, Jean-Loup; Gagnol, Alain; Gagnol, Alain; Harden, Marcia Gay; Huston, Anjelica; Modine, Matthew; Blanc, Dominique, 1956-; Salomone, Bruno, 1970-; Benguigui, Jean, 1944- (New Video : GKids, 2012)
In Paris, a cat who lives a secret life as a cat burglar's aide must come to the rescue of Zoe, a neighborhood girl whose mother is a police superintendent, after she falls into a gangster's clutches.